‘Seller or scammer’ : effect of risk communications on the online shoppers’ behaviour of guarding against scams - Ng, Rachel Li En (2018)
Given the rise in online shopping scams (Loh, 2016) despite current preventive efforts, this study aimed to understand which characteristics of a shopper might cause him/her to be less wary of scams, so that vulnerable consumers can take more precaution; and to investigate the use of risk communications to increase awareness of scam indications on consumer-to-consumer websites. The effectiveness of fear appeals and two related theories: Protection Motivation Theory (PMT; Rogers, 1975, 1983) and Theory of Reasoned Action (TRA; Fishbein & Ajzen, 1977) in increasing awareness were studied. Participants recruited from the Research Participant pool and from the author’s personal contacts were asked which listing they would avoid on a mock shopping website. This was a naturalistic measurement of whether participants were aware of the indications that a listing could be a scam. Results showed higher Prolonged Stress Reactivity predicted lower awareness while higher Stress Reactivity to Work Overload and higher Negative Affect predicted higher awareness. Participants were again asked which listing they would avoid after being presented with an awareness-raising poster. Results showed that using fear appeals significantly increased awareness when an effective response against the threat was explicitly written (Leventhal, Singer, & Jones, 1965) because the intention-behaviour gap was overcome (Sniehotta, Scholz, & Schwarzer, 2005). Adding statements based on the PMT or TRA increased awareness when the effective response was less explicitly worded. Recommendations were thus made to provide explicit instructions and use the PMT or TRA on risk communications (e.g. posters) to make awareness-raising efforts effective.